2018
DOI: 10.1080/14767058.2018.1481033
|View full text |Cite
|
Sign up to set email alerts
|

Maternal age trends support uptake of non-invasive prenatal testing (NIPT) in the low-risk population

Abstract: Purpose: To examine trends in patients submitting samples for cell-free DNA screening to determine whether they reflect a shift towards NIPT use in the low-risk population. Methods: A review of demographic information was performed for all specimens submitted to the Ariosa Diagnostics clinical laboratory for the Harmony V R prenatal test between January 1, 2014 and December 30, 2017. The proportions of specimens for patients under 35 years and 35 years and older were compared. Results: There was a significant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 16 publications
(12 reference statements)
4
11
0
Order By: Relevance
“…An overall increase in the percentage of tests performed in women younger than 36 years was observed. This corresponds with Chen et al 27 who reported a significant increase in the number of samples received from 65 countries for commercial NIPT from women aged 35 years and younger. 27 One explanation for the increase among women under 36 years old is that in 2015 the reimbursement of FCT for women over 36 years was revoked.…”
Section: Discussionsupporting
confidence: 89%
“…An overall increase in the percentage of tests performed in women younger than 36 years was observed. This corresponds with Chen et al 27 who reported a significant increase in the number of samples received from 65 countries for commercial NIPT from women aged 35 years and younger. 27 One explanation for the increase among women under 36 years old is that in 2015 the reimbursement of FCT for women over 36 years was revoked.…”
Section: Discussionsupporting
confidence: 89%
“…In the current study, women of YMA with no clinical indication accounted for 39.6%, which is almost equal to that in women with AMA. This situation reflected the increase in uptake of NIPT in the low-risk population to some extent, as suggested by Chen et al 16 On comparing the detection rates between women of YMA and AMA, the total PPV for T21 and T18 for women with AMA was found to be significantly higher than that in women with YMA, regardless of whether other indications were considered or not; however, for T13 and SCAs, there was no significant difference, which emphasized the agespecific risk for T18 and T21. 17 However, no significant upward trend of PPVs was observed when pregnant women were subgrouped with an age interval of 5 years.…”
Section: Discussionsupporting
confidence: 55%
“…Ultrasound features of MX were significantly associated with a true‐positive result. This is not a novel finding; however, with NIPT becoming an increasingly popular choice for both low and high priori risk populations, 22,23 it does highlight the continuing importance of a thorough 11 to 14 weeks ultrasound examination after cfDNA testing. We also detected a significant association between the type of confirmatory test used and the likelihood of a false‐positive result.…”
Section: Discussionmentioning
confidence: 99%